Métodos de aprendizagem em educação nutricional para escolares: uma revisão de literatura - (:unkn) unknown (Universidade Federal do Pampa, 2017)
Food and nutritional education is seen as a strategy to promote healthy eating habits and it is believed that school is an appropriate space to develop these actions. The pedagogical strategies promoted, combined with the life experiences to which the individual is exposed, trigger processes such as neuroplasticity, modifying the brain structure of the learner. The objective of this study was to describe nutritional education methods according to their applied learning in schoolchildren. A literature review was conducted in which articles published between 2010 and 2017 were selected, considering articles with applied interventions. The results pointed out after the interventions showed positive reactions, however, it is necessary to apply validated evaluation methods based on scientific evidences through Neuroscience studies that demonstrate the change and effective interference in learning for each method of nutritional education.
Methods of learning in nutritional education for schools: a literature review
Keywords: Educação e neurociência; Education and neuroscience; Educação nutricional; Escolares; Aprendizagem; Nutrition education; School Children; Learning; CNPQ::CIENCIAS DA SAUDE